2021
DOI: 10.3389/fpain.2021.689314
|View full text |Cite
|
Sign up to set email alerts
|

Chemokines and Pain in the Trigeminal System

Abstract: Chemotactic cytokines or chemokines are a large family of secreted proteins able to induce chemotaxis. Chemokines are categorized according to their primary amino acid sequence, and in particular their cysteine residues that form disulphide bonds to maintain the structure: CC, CXC, CX3C, and XC, in which X represents variable amino acids. Among their many roles, chemokines are known to be key players in pain modulation in the peripheral and central nervous systems. Thus, they are promising candidates for novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…Noteworthy femaleselective BPs including cytokine/chemokine production and signaling as well as angiogenesis. The contribution of various cytokine/chemokines in nociception and inflammation (103)(104)(105) is widely established and our data showed that the number of cytokine/chemokines altered in female neurons was higher than in males (i.e. 14 in females versus 3 in males).…”
Section: Discussionmentioning
confidence: 63%
“…Noteworthy femaleselective BPs including cytokine/chemokine production and signaling as well as angiogenesis. The contribution of various cytokine/chemokines in nociception and inflammation (103)(104)(105) is widely established and our data showed that the number of cytokine/chemokines altered in female neurons was higher than in males (i.e. 14 in females versus 3 in males).…”
Section: Discussionmentioning
confidence: 63%
“…The TG neurons synthesise chemicals that are conveyed along their axons and released at their peripheral tissue endings and at their central presynaptic axon terminals. 20,86,88,89,107,108 The application of approaches such as those using patch-clamp recording, immunohistochemical and molecular biological methods developed or refined over this period has proven especially valuable. The use of these approaches has led to the identification of these particular chemicals as well as chemicals present in oro-facial tissues innervated by the afferents, the receptors for these chemicals and the influences of these chemical mediators on the excitability of the small-diameter (A-delta; C-fibre) nociceptive afferents.…”
Section: Function In Transmission Of Nociceptive Informationmentioning
confidence: 99%
“…While these afferents commonly contain chemicals such as glutamate and ATP, it has been found that they may vary in their content of neuropeptides such as substance P and CGRP; some nociceptive afferents may be peptidergic and others non-peptidergic (for review, see Refs. [20,35,68,87,88,108]). By the early 2000s, experimental studies in humans as well as animal models had identified several chemicals that can be released from cells and blood vessels in peripheral tissues as a result of noxious stimuli (e.g.…”
Section: Function In Transmission Of Nociceptive Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemokine are key players in pain modulation in the peripheral and central nervous systems [ 52 ]. Their role in trigeminal pain and their pivotal role in PTNP development has been reviewed recently elsewhere [ 53 ]. CCL2 is a proinflammatory chemokine that recruits monocytes, memory T cells and dendritic cells to the site of inflammation [ 54 ] that is also known to be a glial cells mediator [ 55 ].…”
Section: Peripheral Events In the Pathophysiology Of Ptnpmentioning
confidence: 99%